Board Game Cafe Analysed: Analysis on Sales and Games at Dhadhu Cafe - Prabawaseputra, Rafael Agusto; Harisa, Ardiawan Bagus; Gamayanto, Indra (Journal of Games, Game Art, and Gamification, 2025)
This study aims to enhance understanding of the factors influencing sales and game favoured by players at Dhadhu Cafe, a themed board game cafe. Key factors such as operational hours, promotional activities, game preferences, and menus are analysed using data visualization and multiple linear regression to inform strategic decision-making for the business. Despite their classification nature, decision trees and random forests are also applied in mining sales data, with random forest mitigating decision tree overfitting. Findings aligned between multiple linear regression and data visualization, revealing increasing sales on post-COVID-19. Sales peak on Saturdays, with the most effective sales hours observed from 3 to 8 p.m. (mode = 6 p.m.) daily. Promotions significantly impact sales, while other events have minimal effects. Drinks such as tea, yakult lychee, and matcha are dominating the sales as well as French fries. Light and party games, which typically last 15-45 minutes and accommodate 2-4, 2-6, and 2-12 players, are preferred for teaching players. These games often feature abstract and light themes, including mechanics such as dexterity, abstraction, tactics, and dice rolling.